New approaches for subordination and superordination of multivalent functions associated with a family of linear operators - Seon Hye An; Rekha Srivastava; Nak Eun Cho (Miskolc Mathematical Notes)
The aim of this paper is to study some subordination and superordination implication properties for multivalent functions in the open unit disk associated with a family of linear operators. Moreover, we apply the results and techniques presented here to a class of integral operators.